2017
DOI: 10.1093/annonc/mdw623
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and clinical relevance of tumor-infiltrating lymphocytes (TILs) in ductal carcinoma in situ of the breast

Abstract: TILs occur more frequently in the Her-2 positive DCIS. Although we did not find a significant association between TILs and the 10-year risk of IBE, our data suggest that immunotherapies might be considered in subsets of DCIS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
90
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 21 publications
10
90
2
Order By: Relevance
“…In addition, HER2-positive DCIS show a higher TIL score than HER2-negative DCIS. These findings are in agreement with previous studies of the immune microenvironment of DCIS, in which ER-negative tumors showed a trend towards higher immune infiltrates (22,26,27) and HER2 positive tumors were strongly associated with a higher stromal TIL count (22). Despite significant positive associations with histological features that portend a poor prognosis such as high nuclear grade, comedo necrosis, periductal myxoid stroma, ER negativity, and HER2 positivity, no significant association was found in our study between TILs and recurrence.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, HER2-positive DCIS show a higher TIL score than HER2-negative DCIS. These findings are in agreement with previous studies of the immune microenvironment of DCIS, in which ER-negative tumors showed a trend towards higher immune infiltrates (22,26,27) and HER2 positive tumors were strongly associated with a higher stromal TIL count (22). Despite significant positive associations with histological features that portend a poor prognosis such as high nuclear grade, comedo necrosis, periductal myxoid stroma, ER negativity, and HER2 positivity, no significant association was found in our study between TILs and recurrence.…”
Section: Discussionsupporting
confidence: 92%
“…Disease recurrence following DCIS can occur after many years, and although the TIL cohort was enriched for cases with recurrence (30/138, 21.7%) and had a prolonged median follow-up of 89 months (range, 1-304 months), the lack of association between TILs and recurrence requires further investigation in a large cohort with substantial length of follow-up to enable a well-powered multivariate analysis. One such study also failed to find a correlation between TILs and DCIS recurrence (22). However, such analysis is complicated by the likely different implication of TILs in different intrinsic subtypes (28), the different types of lymphocytes present not distinguishable by H&E staining and the difficulty in getting enough cases to make subgroup analysis sufficiently powerful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current analysis of TILs and their significance in DCIS, a significant association was identified between TILs and tumor grade, central necrosis, and negative ER and PR status. These findings are consistent with previous studies (2123). …”
Section: Discussionsupporting
confidence: 94%
“…Like invasive breast carcinoma, some degree of lymphocytic infiltration is often present within or surrounding ducts involved by DCIS [87,88]. Pruneri et al have recently reported on the prevalence and clinical relevance of TILs in DCIS, in a large series with substantial length of follow up [88].…”
Section: Tils In Ductal Carcinoma In Situmentioning
confidence: 99%